ANALISIS YURIDIS PENYELESAIAN KASUS PEMBANTAIAN RAS NUER DI SUDAN SELATAN DITINJAU DARI STATUTA ROMA 1998 - Maria Hana Angelita; Wisnu Aryo Dewanto; Muhammad Insan Tarigan (Perpustakaan Universitas Surabaya, 2024)
Abstract —The international legal provisions for the crime of genocide are regulated in Article 5 of the 1998 Rome Statute. The massacre case that occurred in South Sudan can be categorized as a crime of genocide primarily because it specifically attacked a particular group, namely the Nuer Race. South Sudan is not a state party to the 1998 Rome Statute. Judicial developments regarding the case until 2019 have not been resolved even though action has been taken by the African Union, so it is indicated that there is a condition of 'Unwilling' by South Sudan regarding the resolution of the case. The aim of this research is to provide a juridical analysis of whether the ICC as a complementary judicial institution with national jurisdiction can play a role in resolving cases even though South Sudan is not a party state. The research results refer to Article 12 paragraph 3 of the 1998 Rome Statute that the ICC has the authority to play a role in resolving cases as regulated in Article 13 letter b of the 1998 Rome Statute through the 'proprio motu' authority to the ICC Prosecutor to carry out investigations. Keywords: rome statute 1998, icc, crime of genocide, massacre of the nuer race south sudan, proprio motu Abstrak—Ketentuan hukum secara internasional dari kejahatan genosida diatur dalam Pasal 5 Statuta Roma 1998. Kasus pembantaian yang terjadi di Sudan Selatan dapat dikategorikan sebagai suatu kejahatan genosida utamanya karena secara khusus menyerang terhadap suatu kelompok tertentu yaitu pembantaian Ras Nuer. Sudan Selatan bukan merupakan negara pihak dalam Statuta Roma 1998. Perkembangan peradilan terhadap kasus hingga 2019 tidak terselesaikan meski telah ditindak oleh African Union, sehingga diindikasikan terdapat kondisi ‘Unwilling’ oleh Sudan Selatan terhadap penyelesaian kasus. Tujuan dari penelitian ini ingin memberikan analisis yuridis apakah ICC selaku lembaga peradilan pelengkap yurisdiksi nasional dapat turut berperan dalam penyelesaian kasus meski Sudan Selatan bukan merupakan negara pihak. Hasil penelitian mengacu pada Pasal 12 paragraf 3 Statuta Roma 1998 bahwa ICC memiliki kewenangan untuk ikut berperan dalam penyelesaian kasus sebagaimana yang diatur dalam Pasal 13 huruf b Statuta Roma 1998 melalui adanya kewenangan ‘proprio motu’ kepada Jaksa ICC untuk melakukan investigasi. Kata kunci: statuta roma 1998, icc, kejahatan genosida, pembantaian ras nuer sudan selatan, proprio motu